Acute Hepatic Porphyrias: Review and Recent Progress. Issue 2 (20th December 2018) - Wang, Bruce; Rudnick, Sean; Cengia, Brent; Bonkovsky, Herbert L.
Abstract : The acute hepatic porphyrias (AHPs) are a group of four inherited diseases of heme biosynthesis that present with episodic, acute neurovisceral symptoms. The four types are 5‐aminolevulinic acid (ALA) dehydratase deficiency porphyria, acute intermittent porphyria, hereditary coproporphyria, and variegate porphyria. Their diagnoses are often missed or delayed because the clinical symptoms mimic other more common disorders. Recent results indicate that acute intermittent porphyria, the most severe of the more common types of AHP, is more prevalent than previously thought, occurring in about 1 in 1600 Caucasians, but with low clinical penetrance (approximately 2%‐3%). Here we provide an updated review of relevant literature and discuss recent and emerging advances in treatment of these disorders. Symptomatic attacks occur primarily in females between 14 and 45 years of age. AHP is diagnosed by finding significantly elevated levels of porphyrin precursors ALA and porphobilinogen in urine. Acute attacks should be treated promptly with intravenous heme therapy to avoid the development of potentially irreversible neurologic sequelae. All patients should be counseled about avoiding potential triggers for acute attacks and monitored regularly for the development of long‐term complications. Their first‐degree relatives should undergo targeted gene testing. Patients who suffer recurrent acute attacks can be particularly challenging to manage. Approximately 20% of patients with recurrent symptoms develop chronic and ongoing pain and other symptoms. We discuss newer treatment options in development, including small interfering RNA, to down‐regulate ALA synthase‐1 and/or wild‐type messenger RNA of defective genes delivered selectively to hepatocytes for these patients. We expect that the newer treatments will diminish and perhaps obviate the need for liver transplantation as treatment of these inborn metabolic disorders. Abstract : The Treatment: Acute hepatic porphyrias are a group of four inherited disorders characterized by a defect in normal hepatic heme synthesis. They may give rise to severe or fatal episodes of severe pain or other neurological features. It is important that physicians consider the diagnosis and perform appropriate testing, especially for urinary ALA and PBG. Treatment has involved dextrose, IV heme and analgesics, but newer treatments with siRNA and/or RNA for the defective genes are under development and may soon provide welcome new alternatives for management.